Geopolitical implications of the thelephone Bogota – Medellin, inaugurated in 1926 - Camargo Uribe, Juan Arturo (Folios, revista de la Facultad de Comunicaciones y Filología, 2012)
In this article we discuss the relationship between the processes of construction of telecommunications networks and some concomitant social and institutional dynamics in a specific technological change process. In order to achieve this we recount aspects of the history of the telephone link between Bogota and Medellin, inaugurated by President Pedro Nel Ospina (1922-1926) days before handing over power and returning to his home in Medellin, which despite its symbolic and practical importance we know very little. The history of this socio-technical artifact interweaves heterogeneous processes of nation building and globalization, since electrical communications are a major material factor in social configuration. At the analytical level, the text also aims to explore some of the theoretical ideas of the field of technology studies about the agency of artifacts in social development, as well as its historical relationship with the construction of Nation in Colombia.